Gender, language and ideology : a genealogy of Japanese women's language - Nakamura, Momoko, 1955- (Discourse approaches to politics, society, and culture., 2014)
The book examines women's language as an ideological construct historically created by discourse. The aim is to demonstrate, by delineating a genealogy of Japanese women's language, that, to deconstruct and denaturalize the relationships between gender and any language, and to account for why and how they are related as they are, we must consider history, discourse and ideology. The book analyzes multiple discourse examples spanning the premodern period of the thirteenth century to the immediate post-WWII years, mostly translated into English for the first time, locating them in political, social and academic developments and describing each historical period in a manner easily accessible for those readers not familiar with Japanese history. This is the first book that describes a comprehensive development of Japanese women's language and will greatly interest students of Japanese language, gender and language studies, linguistics, anthropology, sociology, and history, as well as women's studies and sexuality studies.